Effect of Fenton Operating Conditions on the Performance of the Combined Fenton-SBR Process for Antibiotic Wastewater Treatment - Chaudhuri, M.; Elmolla, E. S. (2010)
The study was undertaken to examine the effect of H2O2/Fe2+ molar ratio as one of the important operating conditions on the performance of the combined Fenton-SBR process for antibiotic wastewater treatment. The SBR was fed with Fenton-treated antibiotic wastewater under five H2O2/Fe2+ molar ratio (10, 20, 50, 100 and 150). As H2O2/Fe2+ molar ratio decreases (increase of Fe2+ concentration), BOD5/COD ratio of the Fenton-treated effluent increases, and SBR and overall efficiency. The SBR efficiency was observed to be very sensitive to BOD5/COD ratio below 0.40. The SBR efficiency in terms of sCOD removal decreased from 68±2% at 0.49±0.01(H2O2/Fe2+ molar ratio 10) to 36±3% at 0.17±0.01 (H2O2/Fe2+ molar ratio 150). The best H2O2/Fe2+ molar ratio for treatment of the antibiotic wastewater in this study was observed to be 20. At Fenton-SBR operating conditions (H2O2/Fe2+ molar ratio 20, H2O2/COD molar ratio 2.5, pH 3 and 30 min Fenton reaction time, and 24 hr hydraulic retention time in SBR), the combined Fenton-SBR efficiency (overall) was 86% as sCOD and final sCOD was 78±4 mg/L, which meets the requirements of the Malaysian Standard (B).